18F-FDG PET/CT in non-small-cell lung cancer patients: a potential predictive biomarker of response to immunotherapy. Issue 8 (August 2019) - Evangelista, Laura; Cuppari, Lea; Menis, Jessica; Bonanno, Laura; Reccia, Pasquale; Frega, Stefano; Pasello, Giulia
Abstract : Aim: The aim of this study was to assess the predictive role of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) in the evaluation of response to immunotherapy in patients affected by metastatic lung cancer. Materials and methods: From a single-center database, data for 32 patients (median age: 69 years; range: 37–78) with metastatic lung cancer were retrospectively retrieved. All patients were treated with nivolumab. PD-L1 expression was available in 19/32 patients. All patients underwent 18 F-FDG PET/CT before immunotherapy. Whole-body maximum standardized uptake value (SUVmaxwb ), metabolic tumor volume (MTVwb ), and total lesion glycolysis (TLGwb ) were obtained as the sum of SUVmax, metabolic tumor volume, and total lesion glycolysis in all metabolic lesions. The best response to therapy was considered in terms of partial response (PR), stable disease (SD), and progressive disease (PD) on the basis of clinical and radiological follow-up. Results: 18 F-FDG PET/CT was positive in 30/32 (94%) patients. The majority of them had a pathological 18 F-FDG uptake in the lung, lymph nodes, and bones. SUVmaxwb, MTVwb, and TLGwb were higher in patients with a positive PD-L1 expression than those with negative expression. Twenty-one patients achieved disease control (PR+SD), whereas 11 did not (PD). SUVmaxwb was significantly higher in patients without a response to therapy than those with a response to immunotherapy (median: 48.97 vs. 20.85; Student t -test: P = 0.002). Similarly, TLGwb and MTVwb were also higher in nonresponders than responders, although not statistically significant. However, the difference was more evident in women than men (median SUVmaxwb in responders and nonresponders for women and men: 17.86 vs. 85.89 and 21.38 vs. 44.38, respectively). Conclusion: The entire tumor burden evaluated by 18 F-FDG PET/CT can be predictive of response to immunotherapy in patients with metastatic lung cancer. A large prospective multicenter trial is warranted to definitively assess the usefulness of 18 F-FDG PET/CT as a predictive biomarker of response to immunotherapy. Abstract : Supplemental Digital Content is available in the text.